The Oxford handbook of New Testament, gender, and sexuality - Dunning, Benjamin H. (Oxford University Press, 2019)
"The Oxford Handbook of Gender and Sexuality in the New Testament provides a roadmap to the relevant problems, debates, and issues that animate the study of sex, gender, sexuality, and sexual difference in early Christianity. Leading scholars in the field offer original contributions by way of synthesis, critical interrogation, and proposals for future research trajectories." (Verlagsinformation)